Propuesta de un modelo financiero para aplicar al sector salud en Costa Rica - Acevedo-Castellón, Róger; Giralt-Fallas, Rodolfo; Vargas, Jonathan (Instituto Tecnológico de Costa Rica, 2015)
In Costa Rica, the study of Finances applied specifically to the Health Sector is a relatively new subject. Even though during the past years, a further analysis and depth of different financial tools and techniques has been achieved, it has been focused primarily in the industrial and commercial sector of the country. Given the importance the Health Sector has had historically in the development of the country, since it has been an integral part of its growth plans and has contributed to achieving better social indicators, we consider that the appliance of advanced financial techniques focused specifically in the health sector can contribute to reinforce further its development. This work tries to do a diagnosis of the sector and then an analysis for a specific component of the system, which is the Hospital del Trauma, with the purpose of providing recommendations about the techniques that will allow it to have a better control and development, contributing to a further knowledge of specific financial analysis for this sector.
Proyecto de Graduación (Maestría en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2015.
Keywords: Estructura financiera; Análisis vertical; Análisis horizontal; Hospital del Trauma; Análisis financiero; Indicadores financieros